Gravity Waves in Global High‐Resolution Simulations With Explicit and Parameterized Convection. Issue 8 (29th April 2019) - Stephan, C. C.; Strube, C.; Klocke, D.; Ern, M.; Hoffmann, L.; Preusse, P.; Schmidt, H.
Abstract: Increasing computing resources allow us to run weather and climate models at horizontal resolutions of 1–10 km. At this range, which is often referred to as the convective gray zone, clouds and convective transport are partly resolved, yet models may not achieve a satisfactory performance without convective parameterizations. Meanwhile, large fractions of the gravity wave (GW) spectrum become resolved at these scales. Convectively generated GWs are sensitive to spatiotemporal characteristics of convective cells. This raises the question of how resolved GWs respond to changes in the treatment of convection. Two global simulations with a horizontal grid spacing of 5 km are performed, one with explicit and one with parameterized convection. The latitudinal profiles of absolute zonal‐mean GW momentum flux match well between both model configurations and observations by satellite limb sounders. However, the simulation with explicit convection shows ∼30–50% larger zonal‐mean momentum fluxes in the summer hemisphere subtropics, where convection is the dominant source of GWs. Our results imply that changes in convection associated with the choice of explicit versus parameterized convection can have important consequences for resolved GWs, with broad implications for the circulation and the transport in the middle atmosphere. Key Points: Parameterized convection reduces the stratospheric zonal‐mean zonal gravity wave momentum flux Explicit convection is associated with stronger updrafts and gravity wave sources Spectral changes result from more variable precipitation in the simulation with explicit convection